Precalculus : graphical, numerical, algebraic.: graphical, numerical, algebraic. (2022) - Demana, Franklin D, 1938-; Waits, Bert K; Foley, Gregory D; Kennedy, Daniel, 1946-; Bock, David E
No abstract available